Chemically reactive membrane crystallisation reactor for CO2–NH3 absorption and ammonium bicarbonate crystallisation: Kinetics of heterogeneous crystal growth - Bavarella, Salvatore; Brookes, Adam; Moore, Andrew; Vale, Peter C. J.; Di Profio, Gianluca; Curcio, Efrem; Hart, Phil; Pidou, Marc; McAdam, Ewan J. (Elsevier, 2019)
The feasibility of gas-liquid hollow fibre membrane contactors for the chemical absorption of carbon dioxide (CO2) into ammonia (NH3), coupled with the crystallisation of ammonium bicarbonate has been demonstrated. In this study, the mechanism of chemically facilitated heterogeneous membrane crystallisation is described, and the solution chemistry required to initiate nucleation elucidated. Induction time for nucleation was dependent on the rate of CO2 absorption, as this governed solution bicarbonate concentration. However, for low NH3 solution concentrations, a reduction in pH was observed with progressive CO2 absorption which shifted equilibria toward ammonium and carbonic acid, inhibiting both absorption and nucleation. An excess of free NH3 buffered pH suitably to balance equilibria to the onset of supersaturation, which ensured sufficient bicarbonate availability to initiate nucleation. Following induction at a supersaturation level of 1.7 (3.3 M NH3), an increase in crystal population density and crystal size was observed at progressive levels of supersaturation which contradicts the trend ordinarily observed for homogeneous nucleation in classical crystallisation technology, and demonstrates the role of the membrane as a physical substrate for heterogeneous nucleation during chemically reactive crystallisation. Both nucleation rate and crystal growth rate increased with increasing levels of supersaturation. This can be ascribed to the relatively low chemical driving force imposed by the shift in equilibrium toward ammonium which suppressed solution reactivity, together with the role of the membrane in promoting counter-current diffusion of CO2 and NH3 into the concentration boundary layer developed at the membrane wall, which permitted replenishment of reactants at the site of nucleation, and is a unique facet specific to this method of membrane facilitated crystallisation. Free ammonia concentration was shown to govern nucleation rate where a limiting NH3 concentration was identified above which crystallisation induced membrane scaling was observed. Provided the chemically reactive membrane crystallisation reactor was operated below this threshold, a consistent (size and number) and reproducible crystallised reaction product was collected downstream of the membrane, which evidenced that sustained membrane operation should be achievable with minimum reactive maintenance intervention.
Keywords: Nucleation; Solid phase; Chemical absorption; Precipitation; Ammonia